Rapid gas-induced detachable rGO/MnO debonding layer for flexible electronic applications. (May 2019) - Kim, Young Bae; Hong, Tae Hyun; Sheng, Jiazhen; Park, Hun; Noh, Sung Hyun; Ambade, Swapnil B.; Eom, Wonsik; Park, Jin-Seong; Han, Tae Hee
Abstract: In flexible display technology, the electronic components are constructed on a flexible polymer substrate film and are released from a carrier glass with the detachment of the polymer film. During the debonding process, however, strong polymer-glass bonding often causes the formation of wrinkles and buckles of the polymer film and thereby the damage of electronics. Here, we report on a novel debonding layer (DBL) of graphene/MnO hybrids for scalable and stable detachment of the polymer film. The DBL acted to decrease the polymer-glass bonding strength. The weakly bonded polymer film was safely detached from the glass in ∼170 s by gas-evolution at DBL. The gas-induced debonding (GID) process was functional in H2 O2 solution, not in other tested solutions, indicating its good solution selectivity. As proof of concept, flexible thin-film transistors (TFTs) were fabricated using our DBL and exhibited the similar transfer characteristics before and after the GID process. We believe our DBL will also pave the ways for flexible photovoltaic cells, flexible flash memories and flexible sensor arrays as well as flexible displays. Graphical abstract: Gas generation by graphene-hybrids in H2 O2 solution and its utilization for the delamination of flexible devices. Image 1